2011
DOI: 10.1371/journal.pone.0022715
|View full text |Cite|
|
Sign up to set email alerts
|

Differential Effects of Prenatal Stress in 5-Htt Deficient Mice: Towards Molecular Mechanisms of Gene × Environment Interactions

Abstract: Prenatal stress (PS) has been shown to influence the development of the fetal brain and to increase the risk for the development of psychiatric disorders in later life. Furthermore, the variation of human serotonin transporter (5-HTT, SLC6A4) gene was suggested to exert a modulating effect on the association between early life stress and the risk for depression. In the present study, we used a 5-Htt×PS paradigm to investigate whether the effects of PS are dependent on the 5-Htt genotype. For this purpose, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
98
2
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 76 publications
(112 citation statements)
references
References 91 publications
9
98
2
3
Order By: Relevance
“…For this particular study, only brain tissue of female PS offspring was used. As shown before by our group [20,22], when using this particular prenatal restraint stress paradigm, predominantly female offspring seem to be vulnerable to the effects of PS. Moreover, regarding the animals used in the present study, when stratifying for sex, the PS effect as observed in the FST was only significant for females (F 3, 35 = 0.980, p = 0.329 vs. F 3, 32 = 5.494, p = 0.025, for males and females, respectively).…”
Section: Methodssupporting
confidence: 66%
See 4 more Smart Citations
“…For this particular study, only brain tissue of female PS offspring was used. As shown before by our group [20,22], when using this particular prenatal restraint stress paradigm, predominantly female offspring seem to be vulnerable to the effects of PS. Moreover, regarding the animals used in the present study, when stratifying for sex, the PS effect as observed in the FST was only significant for females (F 3, 35 = 0.980, p = 0.329 vs. F 3, 32 = 5.494, p = 0.025, for males and females, respectively).…”
Section: Methodssupporting
confidence: 66%
“…When the offspring reached the age of 2 months (P60), behavioral experiments were started (n = 10-14/group), as reported in detail previously [22]. Briefly, first, memory abilities were assessed using the object recognition task, after which anxiety- and depressive-like behavior were tested using the elevated zero maze test and FST, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations